Assessing the effectiveness of the Environmental Impact Assessment (EIA) process as a protective measure for indigenous plant species within the Sandveld area, from a conservation perspective - Dyers, Grant Kevern (Department of Environmental and Geographical Science, 2023)
The Cape Floristic Region is a world-renowned hotspot for biodiversity. Due to its ecological importance, there is a need to protect and conserve an area such as the Sandveld area, which falls within the Cape Floristic Region, for the current and future generations to be able to not only benefit from these natural resources but also bask in the glorious sights of these indigenous plants. As a result of the increased demand for rooibos, potatoes, and other produce, many land users are illegally clearing indigenous vegetation within the Sandveld. In the potato sector, the soil pathogens and escalating input costs involved with maintaining centre pivots, pressure land users to clear new lands to safeguard crops, expand yields and sustain the economic sustainability of the farms (Western Cape Government, 2018a). Additionally, in the rooibos sector, the price of tea ultimately drives the demand and supply, when prices are elevated, these offer strong incentives for land users to enlarge their sow to capitalise on the favourable market condition (Western Cape Government, 2018a). This frequently leads to the clearance of new lands without obtaining the prerequired environmental authorisations required for clearing new lands, containing indigenous vegetation. As a result of the intensified agricultural expansion within the area, displays a prime example of the negative effects of non-compliance with environmental legislation and not obtaining the required authorisation before commencing with the clearance of indigenous vegetation. This study unpacks the negative impacts associated with agricultural expansion and its associated clearance of indigenous vegetation within the area. The study further explores the notion of evaluating the effectiveness of the Environmental Impact Assessment (EIA) process as a protective measure for indigenous plant species within the Sandveld area, from a conservation perspective. In addition to the above-mentioned, the study aims to determine whether there are any legal alternatives to the EIA process, for agricultural expansion that impacts the clearance of indigenous vegetation. In determining the above objectives of the study, the study has found that the EIA process is failing the Sandveld area, as a protective measure for indigenous vegetation, from a conservation perspective. It found that it is not predominately the law that is failing the area, but rather the human elements associated with pre-application, assessment process and post- application (approval of Environmental Authorisation). This further highlights that there is a need for improved enforcement and a paradigm shift in the way that the applications and reports are submitted, fueling speculation that specialists and EAPs are being paid by the applicant of the proposed development. The study further discusses the legal alternative to the EIA process, which can assist in the protection of the indigenous vegetation within the Sandveld and CFR, known as the Sandveld Environmental Management Framework (EMF). The EMF allows for the implementation of Farm Level Management Plans; however, these are site-specific and have limitations. After discussing the Sandveld EMF, via a Microsoft Teams call on 2 August 2022, with the DEA&DP officials who drafted the Sandveld EMF document; it was established that the incorporation of landscape approach principles into the Sandveld EMF was never the intention of the document. However, whilst unpacking the document requirements in the discussion, it was raised that many of the landscape approach principles are unintentionally addressed by the process of implementing the Sandveld EMF. Much of the Sandveld EMF mirror valuable principles of the Strategic Environmental Assessment and the ecosystem approach (De Villiers & Hill, 2008). As the study took place during the global pandemic of COVID-19, and face-to-face interviews were not permitted, the study could only be done using a small sample size of 25 interviewees, all of which has some involvement in the protection and conservation of the Western Cape, South Africa indigenous vegetation. These interviewees range from government officials enforcing environmental legislation to environmental assessment practitioners in the field. The interviews were done in the form of electronic questionnaires, tailored to obtain useful information needed for the study.